4CPS-206 Evaluation of therapeutic adherence and determination of the causes of therapeutic non-compliance in renal transplant patients. (2nd March 2018) - Toukabri, I; Majdoubi, M; Mankai, S; Manai, M; Hasni, N; Jeddou, K Ben; Ouachi, Z
Abstract : Background: Therapeutic non-adherence is a major problem in patients with chronic kidney disease. This is the major cause of rejection in renal transplant patients. Purpose: The aim of this work was to evaluate the therapeutic adherence in renal transplant patients and to identify the causes of poor adherence. Material and methods: This was a prospective study carried out on patients hospitalised in the renal transplant unit over a period of 4 months: from 1 April to 31 July 2016. All patients hospitalised during this period are included in the study. The test used to assess therapeutic adherence was Morisky's test. Questioning was conducted for each patient to who were asked to fill inclinical information sheet. Data analysis was done by SPSS. Results: We studied 33 renal transplant patients. The average age of these patients was 43-years-old with extremes ranging from 20 to 59 years old. The number of male patients was 22 (66.6%) and the number of female patients was 11 (33.3%). Twenty-one patients had secondary level of education (63, 3%), seven patients had primary level of education (21.2%) and four patients had university level of education (12%). Only one patient was illiterate (3.03%). Twenty patients had a minimal therapeutic adherence problem, which represents 60.6%. Twelve patients had good compliance (36.4%) and one had poor compliance (3.03%). Several reasons for non-compliance were raised. Forgetting medication represents 15.2%. The important number of drugs leads to therapeutic non-compliance and accounts for 18.2%. The ineffectiveness of the treatment represents a reason for non-compliance and represents 3.03%. The occurrence of adverse events represents 9.09%. The feeling of embarrassment and shyness when taking medication in front of others accounts for 25.7%. Conclusion: Several causes are responsible for non-compliance such as forgetfulness, the multitude of drugs, ineffectiveness, the occurrence of adverse effects and the feeling of shyness when taking medication in front of others. A lot of these barriers are preventable just by better communication between the patient, his doctor and the care system. Therapeutic education is important in improving therapeutic adherance. References and/or Acknowledgements: M. Belrhiti, L. Benamar S. Hacib, A. Abouzoubair. Observance thérapeutique après transplantation rénale:expérience du service de néphrologie du CHU Ibn-Sina de Rabat. 2017. No conflict of interest